Correlation between solar activity and the local temperature of Antarctica during the past 11, 000 years. (January 2015) - Zhao, X.H.; Feng, X.S.
Abstract: The solar impact on the Earth's climate change is a long topic with intense debates. Based on the reconstructed data of solar sunspot number (SSN), the local temperature in Vostok ( T ), and the atmospheric CO2 concentration data of Dome Concordia, we investigate the periodicities of solar activity, the atmospheric CO2 and local temperature in the inland Antarctica as well as their correlations during the past 11, 000 years before AD 1895. We find that the variations of SSN and T have some common periodicities, such as the 208 year (yr), 521 yr, and ~1000 yr cycles. The correlations between SSN and T are strong for some intermittent periodicities. However, the wavelet analysis demonstrates that the relative phase relations between them usually do not hold stable except for the millennium-cycle component. The millennial variation of SSN leads that of T by 30–40 years, and the anti-phase relation between them keeps stable nearly over the whole 11, 000 years of the past. As a contrast, the correlations between CO2 and T are neither strong nor stable. These results indicate that solar activity might have potential influences on the long-term change of Vostok's local climate during the past 11, 000 years before modern industry. Highlights: SSN and Vostok temperature ( T ) had common periodicities in past 11, 000 years. The millennial variations of SSN and T had a strong and stable correlation. The millennial variation of SSN led that of T by 30–40 years. Correlations between CO2 and T were neither strong nor stable.